Allergic cutaneous reactions to systemic corticosteroids Reações cutâneas alérgicas a corticóides sistêmicos - Raymond Ramirez; Ronald R. Brancaccio (Sociedade Brasileira de Dermatologia, 2007)
Contact allergic reactions to topical corticosteroids are common. Cutaneous hypersensitivity reactions to systemically administered corticosteroids might occur though less frequently. The purpose of this literature review is to examine reported cases of cutaneous reactions to systemically administered corticosteroids. The data are presented considering route of administration, type of drug, type of reaction, and testing results. Corticosteroid classifications, cross-reactions, and allergy testing methods are also discussed. São comuns as reações alérgicas de contato a corticóides tópicos. Podem ocorrer reações cutâneas de hipersensibilidade a corticóides sistêmicos, mas são menos frequentes. O objetivo desta revisão da literatura é examinar relatos de casos de reações cutâneas a corticóides sistêmicos. Os dados apresentados levam em consideração a via de administração, tipo de medicamento, tipo de reação e resultados dos testes. A revisão discute também sobre classificações de corticóides, reações cruzadas e testes alérgicos.